Where We Stand: Lung Organotypic Living Systems That Emulate Human-Relevant Host–Environment/Pathogen Interactions - Jimenez-Valdes, Rocio J.; Can, Uryan I.; Niemeyer, Brian F.; Benam, Kambez H. (Frontiers in Bioengineering and Biotechnology, 2020)
Lung disorders such as chronic obstructive pulmonary disease (COPD) and lower respiratory tract infections (LRTIs) are leading causes of death in humans globally. Cigarette smoking is the principal risk factor for the development of COPD, and LRTIs are caused by inhaling respiratory pathogens. Thus, a thorough understanding of host-environment/pathogen interactions is crucial to developing effective preventive and therapeutic modalities against these disorders. While animal models of human pulmonary conditions have been widely utilized, they suffer major drawbacks due to inter-species differences, hindering clinical translation. Here we summarize recent advances in generating complex 3D culture systems that emulate the microarchitecture and pathophysiology of the human lung, and how these platforms have been implemented for studying exposure to environmental factors, airborne pathogens, and therapeutic agents.